Risk Assessment and Risk Minimization in Nanomedicine: A Need for Predictive, Alternative, and 3Rs Strategies - Accomasso, Lisa; Cristallini, Caterina; Giachino, Claudia (Frontiers in Pharmacology, 2018)
The use of nanomaterials in medicine has grown very rapidly, leading to a concern about possible health risks. Surely, the application of nanotechnology in medicine has many significant potentialities as it can improve human health in at least three different ways: by contributing to early disease diagnosis, improved treatment outcomes and containment of health care costs. However, toxicology or safety assessment is an integral part of any new medical technology and the nanotechnologies are no exception. The principle aim of nanosafety studies in this frame is to enable safer design of nanomedicines. The most urgent need is finding and validating novel approaches able to extrapolate acute in vitro results for the prediction of chronic in vivo effects and to this purpose a few European initiatives have been launched. While a ‘safe-by-design’ process may be considered as utopic, ‘safer-by-design’ is probably a reachable goal in the field of nanomedicine.